Mesenteric lymph reperfusion after superior mesenteric artery occlusion shock exacerbates endotoxin translocation in brain - Zhao,Zi-gang (2014)
PURPOSE: To determine the role of mesenteric lymph reperfusion (MLR) on endotoxin translocation in brain to discuss the mechanism of brain injury subjected to superior mesenteric artery occlusion (SMAO) shock. METHODS: Twenty-four rats were randomly assigned to MLR, SMAO, MLR+SMAO and sham groups. MLR was performed by clamping the mesenteric lymph duct (MLD) for 1 h and then allowing reperfusion for 2 h in the MLR group; SMAO involved clamping the superior mesenteric artery (SMA) for 1 h, followed by reperfusion for 2 h in the SMAO group; occlusion of both the SMA and MLD for 1 h was followed by reperfusion for 2 h in the MLR+SMAO group rats. RESULTS: SMAO shock induced severe increased levels of the endotoxin, lipopolysaccharide receptor, lipopolysaccharide-binding protein, intercellular adhesion molecule-1 and tumor necrosis factor-α. Concurrently, MLR after SMAO shock further aggravates these deleterious effects. CONCLUSION: Mesenteric lymph reperfusion exacerbated the endotoxin translocation in brain; thereby increased inflammatory response occurred, suggesting that the intestinal lymph pathway plays an important role in the brain injury after superior mesenteric artery occlusion shock.